Male and Female in the Epic of Gilgamesh : Encounters, Literary History, and Interpretation - Abusch, I. Tzvi (Book collections on Project MUSE., 2015)
The deeds and struggles of Gilgamesh, legendary king of the city-state Uruk in the land of Sumer, have fascinated readers for millennia. They are preserved primarily in the Epic of Gilgamesh, one of the most well-known pieces of Mesopotamian literature. Studying the text draws us into an orbit that is engaging and thrilling, for it is a work of fantasy and legend that addresses some of the very existential issues with which contemporary readers still grapple. We experience the excitement of trying to penetrate the mind-set of another civilization, an ancient one--in this instance, a civilization that ultimately gave rise to our own.The studies gathered here all demonstrate Tzvi Abusch's approach to ancient literature: to make use of the tools of literary, structural, and critical analysis in service of exploring the personal and psychological dimensions of the narration. The author focuses especially on the encounters between males and females in the story. The essays are not only instructive for understanding the Epic of Gilgamesh, they also serve as exemplary studies of ancient literature with a view to investigating streams of commonality between ancient times and ours.